2012
DOI: 10.1136/annrheumdis-2012-201915
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of apremilast, an oral phosphodiesterase 4 inhibitor, in ankylosing spondylitis

Abstract: Although a small pilot study, these results suggest that apremilast may be effective and well tolerated in AS and modulates biomarkers of bone biology. These data support further research of apremilast in axial inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(63 citation statements)
references
References 32 publications
2
50
0
7
Order By: Relevance
“…1,2,8 Apremilast is a novel, orally available small molecule that inhibits the activity of PDE4, subsequently inhibiting the production of TNF-alpha, IL-2, IL-8, IL-12, IL-23, CXCL9, CXCL10, CCL4, interferongamma, and leukotriene B4 and increasing the production of IL-10. [1][2][3][4][5][8][9][10] The specifi c mechanism(s) by which apremilast exerts its therapeutic action in psoriatic arthritis patients is not well defi ned. 1 Apremilast also suppresses arthritis in rodents and reduces the severity of psoriasiform features in mice with psoriatic xenografts.…”
mentioning
confidence: 99%
“…1,2,8 Apremilast is a novel, orally available small molecule that inhibits the activity of PDE4, subsequently inhibiting the production of TNF-alpha, IL-2, IL-8, IL-12, IL-23, CXCL9, CXCL10, CCL4, interferongamma, and leukotriene B4 and increasing the production of IL-10. [1][2][3][4][5][8][9][10] The specifi c mechanism(s) by which apremilast exerts its therapeutic action in psoriatic arthritis patients is not well defi ned. 1 Apremilast also suppresses arthritis in rodents and reduces the severity of psoriasiform features in mice with psoriatic xenografts.…”
mentioning
confidence: 99%
“…Recently, large double-blind and randomized multicenter studies demonstrated that APM is effective in the treatment of psoriasis, PsA, and AS, with significantly higher numbers of patients achieving the endpoints compared with baseline [Pathan et al 2013;Schett et al 2012]. Anakinra (ANK) (IL-1 receptor antagonist) has been approved for active RA patients and it is useful in many inflammatory diseases [Néel et al 2014;Cantarini et al 2014].…”
Section: Apremilast (Apm) Represents a Molecule That Specifically Tarmentioning
confidence: 99%
“…The IL-6R antagonists tocilizumab and sarilumab [14,15] do not seem to work in AS. In contrast, the anti-IL 17a-antibody secukinumab [16] and the phosphodiesterase-4 inhibitor apremilast may have beneficial effects in AS [17]. On the other hand, in the first reports about the pharmacokinetics, the efficacy and safety of biosimilars in patients with active AS have shown promising results [18].…”
Section: Introductionmentioning
confidence: 99%